下列计算正确的是 ( )
A. a 3 + a 2 = a 5 B. a 3 - a 2 = a C. a 3 · a 2 = a 6 D. a 3 ÷ a 2 = a
下列运算正确的是 ( )
A. 4 x + 5 y = 9 xy B. ( - m ) 3 · m 7 = m 10 C. ( x 2 y ) 5 = x 2 y 5 D. a 12 ÷ a 8 = a 4
A. ( x + y ) 2 = x 2 + y 2 B. ( − 1 2 x y 2 ) 3 = − 1 6 x 3 y 6
C. x 6 ÷ x 3 = x 2 D. ( − 2 ) 2 = 2
A. 5 x - 3 x = 2 B. ( x - 1 ) 2 = x 2 - 1 C. ( - 2 x 2 ) 3 = - 6 x 6 D. x 6 ÷ x 2 = x 4
计算 ( - a ) 6 ÷ a 3 的结果是 ( )
A. - a 3 B. - a 2 C. a 3 D. a 2
A. a 2 · a 3 = a 6 B. a 7 ÷ a 3 = a 4 C. ( a 3 ) 5 = a 8 D. ( ab ) 2 = a b 2
A. ( b 2 ) 3 = b 5 B. x 3 ÷ x 3 = x C. 5 y 3 · 3 y 2 = 15 y 5 D. a + a 2 = a 3
已知 3 m = 4 , 3 2 m - 4 n = 2 .若 9 n = x ,则 x 的值为 ( )
A.8B.4C. 2 2 D. 2
A. a 2 + a 3 = a 5 B. ( a 2 ) 3 = a 5
C. a 4 − a 3 = a D. a 4 ÷ a 3 = a
已知 a m = 3 , a n = 2 ,则 a 2 m − n 的值为 .
A. a 2 + a 3 = a 5 B. a 2 · a 3 = a 5 C. a 3 ÷ a 2 = a 5 D. ( a 2 ) 3 = a 5
A. a 2 · a 3 = a 6 B. a 6 ÷ a - 2 = a - 3
C. ( - 2 a b 2 ) 3 = - 8 a 3 b 6 D. ( 2 a + b ) 2 = 4 a 2 + b 2
A. x 2 · x 3 = x 6 B. x 6 ÷ x 3 = x 3 C. x 3 + x 3 = 2 x 6 D. ( - 2 x ) 3 = - 6 x 3
A. 3 a 2 − a 2 = 3 B. ( a 2 ) 3 = a 6
C. a 2 · a 3 = a 6 D. a 6 ÷ a 2 = a 3
A. ( x + y ) 2 = x 2 + y 2 B. ( x 2 ) 3 = x 5
C. x 2 = | x | D. x 6 ÷ x 2 = x 3